Progress and challenges of contaminate removal from wastewater using microalgae biomass. (January 2022) - Ahmed, Shams Forruque; Mofijur, M.; Parisa, Tahlil Ahmed; Islam, Nafisa; Kusumo, F.; Inayat, Abrar; Le, Van Giang; Badruddin, Irfan Anjum; Khan, T.M. Yunus; Ong, Hwai Chyuan
Abstract: The utilization of microalgae in treating wastewater has been an emerging topic focussed on finding an economically sustainable and environmentally friendly approach to treating wastewater. Over the last several years, different types of con microalgae and bacteria consortia have been experimented with to explore their potential in effectively treating wastewater from different sources. The basic features considered while determining efficiency is their capacity to remove nutrients including nitrogen (N) and phosphorus (P) and heavy metals like arsenic (As), lead (Pb), and copper (Cu). This paper reviews the efficiency of microalgae as an approach to treating wastewater from different sources and compares conventional and microalgae-based treatment systems. The paper also discusses the characteristics of wastewater, conventional methods of wastewater treatment that have been used so far, and the technological mechanisms for removing nutrients and heavy metals from contaminated water. Microalgae can successfully eliminate the suspended nutrients and have been reported to successfully remove N, P, and heavy metals by up to 99.6 %, 100 %, and 13%–100 % from different types of wastewater. However, although a microalgae-based wastewater treatment system offers some benefits, it also presents some challenges as outlined in the last section of this paper. Performance in eliminating nutrients from wastewater is affected by different parameters such as temperature, biomass productivity, osmotic ability, pH, O2 concentration. Therefore, the conducting of pilot-scale studies and exploration of the complexities of contaminants under complex environmental conditions is recommended. Highlights: Utilization of Microalgae is an environment-friendly method to treat the wastewater. Microalgae removes the suspended nutrients and polluting compounds from wastewater. The efficiency of microalgae-based wastewater treatment technology is presented. Challenges of using microalgae in wastewater treatment is discussed.